2008
DOI: 10.1002/j.2048-7940.2008.tb00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Link Between Safe Patient Handling and Patient Outcomes in Long-Term Care

Abstract: This study examined the relationship between safe patient handling and quality of care measures. A comprehensive patient care ergonomics program included six elements. Using a retrospective observational design, 10 quality domains were compared before and after implementation of the program for 111 residents living on 24 units in six Veterans Administration nursing homes using a general linear regression model with repeated measures clustered within time and adjusted for age. After implementation, we found low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…In general, however, a reduction in lost workdays due to injury was also found with ergonomic programme implementation [15,16,18,51], as were reductions in injury-related costs [16,51]. The quality of the study evidence overall is not high; some are small [13,14,41], not randomised [4,16,42,46,49,52], or lacking appropriate controls [4,12,16,17,45,49,50], or include other factors which may have an influence on the study result [44,48,51]. Table 1.…”
Section: In Relation To Healthcare Workers: Ergonomic Devices And/or mentioning
confidence: 98%
See 4 more Smart Citations
“…In general, however, a reduction in lost workdays due to injury was also found with ergonomic programme implementation [15,16,18,51], as were reductions in injury-related costs [16,51]. The quality of the study evidence overall is not high; some are small [13,14,41], not randomised [4,16,42,46,49,52], or lacking appropriate controls [4,12,16,17,45,49,50], or include other factors which may have an influence on the study result [44,48,51]. Table 1.…”
Section: In Relation To Healthcare Workers: Ergonomic Devices And/or mentioning
confidence: 98%
“…No significant improvement was shown in mood or behaviour indicators, however, or cognition. This study relied on secondary data, had no control group, and was also a retrospective analysis [4], so it would be interesting to see what outcomes were achieved from a better-powered study. Owen et al described a self-reported improvement in patient comfort and feeling secure when an ergonomic device was used [6], while Garg & Kapellusch assessed patient ratings of lifting devices, reporting that the majority of patients found the devices to be comfortable and safe [18].…”
Section: In Relation To Patients and Outcomesmentioning
confidence: 99%
See 3 more Smart Citations